Dealing with Common Challenges in Improving Reading Comprehension Skills for Indonesian Secondary School Students - Izzuddin A Hakim; Amazia Pravianti Tanuatmadja; Hodairiyah (ELS Journal on Interdisciplinary Studies in Humanities, 2022)
It is expected that Indonesian secondary school students learn to read in English for fulfilling school requirements (for both learning and testing). However, many students have a problem in reading textbooks caused by the lack of students’ understanding in answering the comprehension questions correctly. This leads to students' lack of interest in reading. Having collected the relevant pieces of literature and data, we concluded that students' motivation, the students' awareness of reading text genre, and the proper implementation of reading strategies are the effective solution to enhance Indonesian secondary students' reading comprehension skills. This study offers some important insights to the research in reading skills not only academically but in daily life. Moreover, the study is to facilitate English teachers in understanding students' reading comprehension problems, what strategies to apply in teaching reading and how to choose the suitable reading text genre to make their students achieve better in their academic performance and to make the students' love reading. Keywords: reading skill, comprehension, secondary school, students